(untitled) (Indian Journal of Public Health Research & Development, 2020)
Introduction: Migration is a process of social change due to which a person moves from one cultural setting to another to settle for a longer period or permanently. The collapse of rural livelihood forces the workers to migrate. As migrants do several types of jobs, there are high chances of morbidities. Methods: A cross-sectional study was done on 392 people selected using simple random sampling in Lingapayyakadu using pre-tested and semi-structured questionnaire. SPSS software was used for data analysis. Results: 68.7% were males and rest females. 80.9% had some form of acute morbidity in previous 3 months whereas 16% were suffering from chronic morbidities. Age (p = 0.046), working hours per day (p = 0.017) and occupation (p = 0.047) had significant association with acute morbidity while age, (p < 0.01) sex (p = 0.046) and education level (p < 0.01) had significant association with chronic morbidity. Conclusion: Major acute morbidity was musculo-skeletal disorders and age, working hours and occupation had significant association while hypertension was the major chronic morbidity with age, sex and education level having significant association with chronic morbidity